Comparative Analysis of Yi Lacquerware Ornamentation in Liangshan and Dafang - Zhao Qiqi; Wan Jamarul Imran bin Wan Abdullah Thani (Studies in Social Science & Humanities, 2024)
This paper explores the evolution of lacquerware ornamentation from traditional to modern expression in two Yi lacquerware regions in China, Liangshan, Sichuan and Dafang, Guizhou, through comparative analysis. Elements from nature, plants, animals and productive life are extracted as the basis of traditional Yi lacquerware ornamentation, focusing on their ornamental nature. However, under the influence of modern civilisation, lacquerware ornamentation has gradually incorporated some creative or modified thematic images, marking a response to the evolving needs of contemporary society. Adopting the sense of order theory and formal analysis theory as theoretical guides, this paper compares the formal characteristics, organisational structure and stylistic expression of lacquerware ornamentation in Liangshan and Dafang, revealing their distinctive visual expressions influenced by culture, history and art.